Relationship Between Pay Assembly Parents With Temper Tantrum In Children Pre School - Retno Dewi Prisusanti; Fita Rusdian Ikawati; Anis Ansyori; Arief Effendi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
The child's relationship with his parents is very important and influences the child's development, including how his mental health. In Indonesia in 2011, toddlers who usually temper tantrums this in one year, 23 - 83% of children aged 2 to 4 years. From the preliminary study results obtained population of research is 65 couples parents and children. Purpose: This study aims to determine whether there is a Parent Parenting Relationship Against Temper Tantrum In Pre-School Children In TK PGRI 2 Malang. Method: This research is analytic research and research design that used is cross sectional research design. Sampling technique in this research is using purposive sampling technique, using questionnaire instrument with sample 55 people. This research uses non parametric data analysis method with statistical test used Chi square table and degress of freedom (DF). Result: From statistic analysis using SPSS calculation with Chi square table and degress of freedom (DF) with 5% significance level(13,341 ≥ 3,481) so that H0 in rejected means there is relation between parenting parenting with temper tantrum in pre school children in TK PGRI 2 Malang City Year 2017. Conclusion: Increase knowledge about parenting parenting and temper taantrum in children through follow counseling, reading books, brochures and leaflets.